ORGANIZATIONAL AND ECONOMIC MECHANISM FOR INTRODUCTION OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN RUSSIA - A. V. Alexeev (Новые технологии, 2020)
In modern conditions artificial intelligence technologies are actively developed and used around the world. The accelerated development of artificial intelligence technologies over the past years suggests paying attention to the problems of introducing artificial intelligence systems into the system of state and municipal government in Russia. The effectiveness of Russian state and municipal government depends on the performance of state and municipal authorities, on the resource intensity of their management decisions. Currently, the improvement of the Russian system of state and municipal government is carried out against the background of the development and implementation of artificial intelligence technologies.The purpose of the article is to determine the requirements for the organizational and economic mechanism for introducing artificial intelligence technologies in Russia. To achieve the goal, the tasks of determining the demand for artificial intelligence technologies in Russia, highlighting the problems of implementing information and communication technologies in public administration are being addressed. The methodological basis of the study are systemic and empirical approaches. The theoretical and methodological basis of the study are works of domestic and foreign authors in the field of artificial intelligence, the implementation of information and communication technologies in the public administration system. The result of the study is determination of the requirements for the organizational and economic mechanism for implementing artificial intelligence technologies and the proposed theoretical model of the organizational and economic mechanism for introducing artificial intelligence technologies in Russia.